(untitled) (Pedagogy of Higher and Secondary Education, 2022)
Conception o f development o f national design to 2010 year: problems of preparation and retraining of specialists. Bases of development of designer activity in Ukraine related to theoretical are formulated in the article and grounded, proektnymy and methodical directions of works. An orientation and maintenance of teaching at preparation of specialist is determined.